Notre Dame at 175 : A Visual History - Lamb, Charles (Book collections on Project MUSE., 2017)
To commemorate the 175th anniversary of the founding of the University of Notre Dame, Charles Lamb and Elizabeth Hogan, both photograph archivists for the university, have chosen 175 images that illustrate the evolution of campus culture and its physical environment. Important pieces of Notre Dame's rich history are highlighted, along with depictions of everyday life on the beautiful campus. Each image is accompanied by a caption explaining why it is historically and artistically significant. Lamb and Hogan have taken care to find images that have not been featured in previous pictorial collec.